Sistem Segmentasi Keluhan Air Bersih di PT. Suryacipta Swadaya Menggunakan K-Medoids Clustering - Reza Noviandi; Yulison Herry Chrisnanto; Herdi Ashaury (Ikatan Ahli Informatika Indonesia, 2020)
Suryacipta Swadaya is a company that manages industrial estates. PT. Suryacipta Swadaya manages water in the industrial area to be distributed to 73 companies in the industrial area. Water in the industrial area sometimes has problems that companies complain about. There are 7 types of complaints with an average of complaints from 2017 to 2019, which is 8929 complaints per year. Water complaints for each company vary in the amount of distribution, however the water needs of each company are different even for the same company that has a diversity of water needs each year. Based on this, PT. Suryacipta Swadaya has difficulty mapping the water complaints group based on company needs, so that it is effective in handling water complaints in the industrial area. In this study the grouping of water complaints will be assisted using the K-Medoids method in the process of grouping water complaints so that the handling process can be handled immediately.